Sistem Ketertelusuran Digital: - Julia Kurniasih (Jurnal Dinamika Informatika, 2023)
Technological innovation makes the traceability system as one of the key factors in the supply chain. The adoption of transformative technologies in harmony with information standards can form a comprehensive digital traceability system and ensure data consistency in the supply chain. Technology can support a traceable information environment to become transparent thereby increasing consumer confidence. The establishment of transparency in the supply chain will increase business productivity through a traceability system that is safe, sustainable, efficient, and inclusive